PENERAPAN NILAI MORAL KEAGAMAAN MELALUI PEMBELAJARAN BERBASIS ALAM BERTEMA LINGKUNGAN DI TK NEGERI PEMBINA TAMBAN BARU TIMUR - Fatimah, Siti; Nisa, Uswatun; Baiti , Noor; Zulkarnaen, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the improvement of religious and moral values among Group B children through nature-based learning with an environmental theme at TK Negeri Pembina Tamban Baru Timur. The study employed a descriptive approach involving 12 Group B children. Data were collected through observation, interviews, and documentation and analyzed descriptively based on children’s developmental achievements.The results showed that nature-based learning effectively improved children’s religious and moral values. Before implementation, 1 child (8.3%) was in the Undeveloped category, 7 children (58.3%) were in the Beginning to Develop category, and 4 children (33.3%) were in the Developing as Expected category. After implementation, the Undeveloped category decreased to 0%, the Beginning to Develop category decreased to 25%, the Developing as Expected category increased to 50%, and the Very Well Developed category increased to 25%. Overall, the percentage of children achieving the Developing as Expected and Very Well Developed categories increased from 33.3% to 75%. These findings indicate that nature-based learning with an environmental theme effectively fosters religious behavior, environmental awareness, and noble character habituation in early childhood.